Emerging Targets in Type 2 Diabetes and Diabetic Complications. Issue 18 (28th July 2021) - Demir, Sevgican; Nawroth, Peter P.; Herzig, Stephan; Ekim Üstünel, Bilgen
Abstract: Type 2 diabetes is a metabolic, chronic disorder characterized by insulin resistance and elevated blood glucose levels. Although a large drug portfolio exists to keep the blood glucose levels under control, these medications are not without side effects. More importantly, once diagnosed diabetes is rarely reversible. Dysfunctions in the kidney, retina, cardiovascular system, neurons, and liver represent the common complications of diabetes, which again lack effective therapies that can reverse organ injury. Overall, the molecular mechanisms of how type 2 diabetes develops and leads to irreparable organ damage remain elusive. This review particularly focuses on novel targets that may play role in pathogenesis of type 2 diabetes. Further research on these targets may eventually pave the way to novel therapies for the treatment—or even the prevention—of type 2 diabetes along with its complications. Abstract : Type 2 diabetes is a complex metabolic disorder associated with a plethora of complications in peripheral organs. This review article highlights the novel targets that might play role in pathogenesis of type 2 diabetes. Further research on these targets might eventually pave the way to novel therapies for the treatment–or even the prevention–of type 2 diabetes.